2011
DOI: 10.4028/www.scientific.net/amr.396-398.624
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Sulfidation of White Lead with Elemental Sulfur

Abstract: Hydrothermal sulfidation of pure white lead with elemental sulfur has been studied in the present paper. The variables considered in the study were temperature, time, particle size and elemental sulfur fraction in the reacting mixture. Temperature and time were the most two important factors, with an increase in temperature and holding time the sulfidation extent of lead improved greatly and the constituent of products changed a lot. At temperatures above 140°C, PbS and PbSO4 were the only stable reaction prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Recently, multiple methods, including mechanochemical processing (Yuan et al, 2012;Li et al, 2017), hydrothermal treatment (Li et al, 2012;Liang et al, 2012) and sulfidation roasting (Li et al, 2010;Zheng et al, 2015;Chen et al, 2019), have been reported for improving the sulfidation performance. Li et al (2017) and Yuan et al (2012) adopted a method of co-grinding lead oxide with sulfur under mild conditions prior to flotation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multiple methods, including mechanochemical processing (Yuan et al, 2012;Li et al, 2017), hydrothermal treatment (Li et al, 2012;Liang et al, 2012) and sulfidation roasting (Li et al, 2010;Zheng et al, 2015;Chen et al, 2019), have been reported for improving the sulfidation performance. Li et al (2017) and Yuan et al (2012) adopted a method of co-grinding lead oxide with sulfur under mild conditions prior to flotation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the floatability of lead oxide cannot be satisfactory attributed to the disproportionation reactions of sulfur, resulting in the formation of PbSO4 and PbS. Liang et al (2012) and Li et al (2012) reported the hydrothermal sulfidation of lead-containing materials and their flotation performance. It was confirmed that the sulfurized lead oxide minerals floated well.…”
Section: Introductionmentioning
confidence: 99%